Go : returning discipleship to the front lines of faith - Sprinkle, Preston M., 1976- (NavPress, 2016)
Disciple-making is a passion of many, as it should be. It is, after all, our great commission. But much of contemporary discipleship is informed by instinct, and as such it is vulnerable to the whims and trends of the broader culture, which can take us further away from our biblical model and mandate. Drawing on a 2015 Barna Group study of the state of discipleship in the United States commissioned by The Navigators, bestselling author Preston Sprinkle provides a holistic, biblical response for discipleship, providing accessible tools for all those who are engaged in making Christ-followers in the 21st century. Sprinkle points pastors, church leaders, and frankly, all Christ-followers, to a discipleship that is responsive to this most current research and accountable to the model of Jesus and his earliest followers, who counted making disciples as their most important work. In an extremely practical fashion, Go helps us to discern, from the Scriptures and from exemplary disciple-making ministries, what discipleship is and is not, what it has become and what it can still be.